THE EFFECT OF INCORPORATING CASSAVA LEAF MEAL WITH FISH MEAL, GROUNDNUT CAKE AND SOYBEAN MEAL BASED DIETS AT THE EXPENSES OF SOYBEAN MEAL ON GROWTH PERFORMANCE AND FEED UTILIZATION OF CATFISH (Clarias gariepinus) - Ibikunle, Femi Lawrence; Ibrahim, Ibrahim Maiyaki; Shuiabu, Danjuma; Azeez, Akeem Aliyu; Ibiyo, Lenient Mercy Onvie; Usman, Aishat Ohunene; Eneche, Ugbede Benedict; Umar, Nasir Ubana; Woru, Hamzat Abubakar; Ekundayo, Toyin Marion; Mohammed, Bello (Journal of Fish Nutrition, 2026)
The potential of cassava leaf meal (CLM) as a partial replacement for soybean meal in the diet of African catfish Clarias gariepinus juveniles was carried out in this study. Six isonitrogenous diets containing 35% crude protein were formulated with graded CLM inclusion levels of 0, 5, 10, 15, 20, and 25%. 630 juveniles were randomly distributed into concrete tanks and fed the experimental diets at 3% body weight for 8weeks in a completely randomized design. Each treatment was replicated thrice for the experiment. Proximate composition and cyanide content of the diets were determined, also, growth performance and nutrient utilization parameters were evaluated. No significant differences (p>0.05) were observed among treatments for growth, feed intake, feed conversion ratio, or protein efficiency ratio. However, fish fed the 10% CLM diet consistently showed higher weight gain, specific growth rate, and protein efficiency ratio compared to other treatments. At higher inclusion levels (≥20%), growth performance and feed efficiency tended to decline, likely due to increased dietary fiber and cyanogenic compounds. These findings indicate that cassava leaf meal can replace soybean meal up to 25% without adverse effects on juvenile catfish performance, with an inclusion level of about 10% appearing most favorable. Cassava leaf meal therefore represents a viable, locally available plant protein source for sustainable aquaculture feed formulation.